(untitled) (British Journal of Global Ecology and Sustainable Development, 2025)
The study of English borrowed words in Uzbek and Dari written sources reveals significant insights into the linguistic adaptation and cultural integration processes in these languages. This paper explores how English terms are incorporated into Uzbek and Dari texts, examining the phonological, morphological, and semantic adjustments that occur. In Uzbek, the assimilation of English vocabulary is often observed in areas related to technology, business, and media, with modifications made to align with the phonetic system of the language. Dari, influenced by English primarily in scientific and academic contexts, shows a similar pattern of adaptation, though the integration is often more direct due to the structural and phonological similarities with English. Through comparative analysis, this study highlights the impact of global communication and modernization on language development, demonstrating how English borrowings serve as a reflection of contemporary societal changes in Uzbekistan and Afghanistan. The findings contribute to a deeper understanding of linguistic borrowing phenomena and the role of English in shaping modern lexical landscapes in Central Asia and the broader region.